145k views
4 votes
(x+12) (3x+2)
Find the value of X

User Kevin Jin
by
5.1k points

2 Answers

4 votes

Explanation:


if \: (x + 12) = (3x + 2) \\ 12 - 2 = 3x - x \\ 2x = 10 \\ x = 5 \\ \\ \\ if(x + 12)(3x + 2) = 0 \\ x + 12 = 0 \: \: \: or \: \: \: 3x + 2 = 0 \\ x = - 12 \: \: \: or \: \: \: x = - (2)/(3)

User Alemv
by
5.8k points
2 votes

Explanation:

Equation at the end of step 1

(3x2 - 38x) + 24 = 0

STEP2:Trying to factor by splitting the middle term

2.1 Factoring 3x2-38x+24

The first term is, 3x2 its coefficient is 3 .

The middle term is, -38x its coefficient is -38 .

The last term, "the constant", is +24

Step-1 : Multiply the coefficient of the first term by the constant 3 • 24 = 72

Step-2 : Find two factors of 72 whose sum equals the coefficient of the middle term, which is -38 .

-72 + -1 = -73 -36 + -2 = -38 That's it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -36 and -2

3x2 - 36x - 2x - 24

Step-4 : Add up the first 2 terms, pulling out like factors :

3x • (x-12)

Add up the last 2 terms, pulling out common factors :

2 • (x-12)

Step-5 : Add up the four terms of step 4 :

(3x-2) • (x-12)

Which is the desired factorization

Equation at the end of step2:

(x - 12) • (3x - 2) = 0

STEP3:Theory - Roots of a product

3.1 A product of several terms equals zero.

When a product of two or more terms equals zero, then at least one of the terms must be zero.

We shall now solve each term = 0 separately

In other words, we are going to solve as many equations as there are terms in the product

Any solution of term = 0 solves product = 0 as well.

Solving a Single Variable Equation:

3.2 Solve : x-12 = 0

Add 12 to both sides of the equation :

x = 12

Solving a Single Variable Equation:

User Ravindra Kushwaha
by
5.6k points